Specific biomarkers for C9orf72 FTD/ALS could expedite the journey towards effective therapies - Rubika Balendra; Thomas G Moens; Adrian M Isaacs (EMBO Molecular Medicine)
Abstract A hexanucleotide repeat expansion in the C9orf72 gene is a common genetic cause of ALS and FTD. The repeats are translated into five different dipeptide repeat proteins (DPRs). In this issue, Lehmer et al (2017) demonstrate that one of these DPRs, poly(GP), can be measured in the CSF of individuals with C9orf72 mutations. In conjunction with the findings from another recent study (Gendron et al, 2017), these DPR biomarkers may prove to be extremely valuable in the quest for effective therapies for C9FTD/ALS.